A Testing Method of Probability Weighting Functions From an Axiomatic Perspective - Takemura, Kazuhisa; Murakami, Hajime (Frontiers in Applied Mathematics and Statistics, 2018)
The aim of this study is to present a testing method to examine various models of probability weighting functions that are considered nonlinear functions of probability in behavioral decision theory, such as prospect theory. Although there are several empirical psychometric tests to examine probability weighting functions, there is no concrete method to examine these functions’ axiomatic properties. We propose axiomatic properties and a testing method to examine the generalized hyperbolic logarithmic model, power model, and exponential power model of the probability weighting functions, and provide an illustrative example of the testing method.